A Non-Instrumental Method to Determine Hydraulic Heads on Low-Lying Coastal Aquifer (Malaysian Journal of Civil Engineering, 2018)
The technique introduced in this paper is to provide an alternative method todetermine hydraulic heads in an unconfined coastal aquifer. The heads could beestablished within a study area without the needs to use any instrument, such as atheodolite. Instead, a less costly small-diameter transparent tube is used toproduce a horizontal plane, formed by a balanced water level in it. Such planesare used as reference levels between two wells on an area, which is relatively flat.Current tidal heights are required in order to calibrate the measurements obtainedfrom the reference levels to the mean sea level. The application of this method atfield as a.case study has revealed the reduction and critical condition of h in thephreatic aquifer of a small island, due to the frequent pumping of the wells.